Rozwój przedsiębiorczości w polityce władz samorządowych : zarys problemu - Wartalska, Magdalena; Moczydłowska, Natalia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The position of territorial self-governmental units in authority and economic system implies the necessity to form conditions for communal and economic development of all parts of self-governmental community. From the character of establishment process management, including the quality of decisions and actions made by self-governmental organs, not only will the supply and quality of public services depend, but more often larger competitiveness of a self-governmental unit in the process of getting different profits such as wining new investors who have big innovational potential. Therefore both in local and regional developmental politics, the creation of the appropriate climate for the generation of entrepreneurship is more important. It is worth to emphasizing that the development of entrepreneurship is supposed to be the main way of reaching the main goal of Lisbon Strategy, that is the formation of competitive, and dynamic economy able to persistent development, based on authority, which will guarantee the commune cohesion. This situation creates the demand for all possible information that would illustrate cooperation mechanisms of business with the territorial self- government. The aim of this article is to only generally specify main aspects connected with the process of creating the conditions for the development of entrepreneurship. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 242-249